C’è arte! Esterházy Péter Olaszországban - Sciacovelli Antonio (Reciti Kiadó, 2025)
Péter Esterházy is certainly one of the most famous authors of contemporary Hungarian literature, even outside Hungary. His reception in Italy dates back to the late 1980s and is based on the fact that some Italian publishers (e/o, Garzanti) have shown considerable interest in Hungarian literature in general, and in this author in particular. In the late 1990s, the appointment of Giorgio Pressburger to head the Budapest Cultural Institute enabled an important cultural and publishing project that led to the translation of many works by the Hungarian writer, especially at Feltrinelli publishing house in Milan. For this reason, literary critics in Italy have also noticed this writer, as evidenced by the many Italian literary awards given to him. In this article, after briefly presenting the basics of the history of Italian-Hungarian cultural relations in the twentieth century, we review the mechanisms that led to the constant presence of Esterházy's works in italian translation, especially since Imre Kertész won the Literature Nobel Prize. Beginning with this award and the huge popularity of the work of Sándor Márai (also in Italy), Italian publishers paid more and more attention to contemporary Hungarian literature.
Külországi könyvespolcokon. Tanulmányok Esterházy Péter idegen nyelvű recepciójáról